Perkembangan Bahasa pada Anak Speechdelay - Jauharoti Alfin; Ratna Pangastuti (JECED : Journal of Early Childhood Education and Development, 2020)
Language development in early childhood is very important for the continuity of his life as a social creature. Incoming language skills have an aspect of early childhood development. This article seeks to discuss the development of speech-based children's language in theory by analyzing documented cases of published research results. The research method used is a library research with content analysis for the discussion technique. Source of data taken from secondary data from research results in thesis or online journals, then combined with several existing theories. Based on the results of the discussion obtained data that children with speech delay will experience language delays both in terms of articulation, sound, fluency and completeness of the preparation of the letters. Many factors as a trigger that is external and internal. Most of the cases that have external factors in the form of parenting are the dominant factors in children experiencing speech delay. Mild speechdelay children can recover with appropriate meode stimulation and selection, while children with medium and large speechdays need the help of experts (therapists) and medical personnel